2008
DOI: 10.1007/s00421-008-0903-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-effect of forward and backward locomotion on body orientation in space during quiet stance

Abstract: Neural circuits responsible for stance control serve other motor tasks as well. We investigated the effect of prior locomotor tasks on stance, hypothesizing that postural post-effects of walking are dependent on walking direction. Subjects walked forward (WF) and backward (WB) on a treadmill. Prior to and after walking they maintained quiet stance. Ground reaction forces and centre of foot pressure (CoP), ankle and hip angles, and trunk inclination were measured during locomotion and stance. In WF compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…Further, walking on a linear treadmill, at variance with overground walking, produces an after-effect on the orientation of the standing body in the form of a forward body inclination lasting for a few minutes [39]. In this case, body inclination would be the consequence of a change in the postural reference arising from treadmill locomotion itself, possibly connected to the peculiarities of this type of walking [40]. Moreover and more interestingly for the present account, when standing subjects oppose for a while a rotational torque applied to the pelvis, an involuntary postcontraction of the trunk muscles is observed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, walking on a linear treadmill, at variance with overground walking, produces an after-effect on the orientation of the standing body in the form of a forward body inclination lasting for a few minutes [39]. In this case, body inclination would be the consequence of a change in the postural reference arising from treadmill locomotion itself, possibly connected to the peculiarities of this type of walking [40]. Moreover and more interestingly for the present account, when standing subjects oppose for a while a rotational torque applied to the pelvis, an involuntary postcontraction of the trunk muscles is observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that periods of 6 minutes treadmill FW or BW have differing acute effects on standing posture with increased forward inclination after FW and backward inclination and centre of pressure position after BW (De Nunzio et al, 2009). Adaptions in FW following BW may demonstrate the adaptability or flexibility of the control systems and it can be suggested that if the two locomotion patterns share the same neural control structures that BW will cause changes in subsequent FW (Choi and Bastian, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the post-effect is not prevented by either a continuous or a post-stimulation visual reference. In this light, the present post-effect would be related to that elicited on body AP orientation by a period of brisk walking on a treadmill, where the post-effect tilt is present when standing both with eyes open and eyes closed, but is larger without vision [31,64]. Another study has shown that the effect of sensory manipulation producing a sway of the body in the frontal plane (by vestibular or cutaneous foot stimulation or the vibration of hip abductors) is not affected by the absence of normal visual information [65].…”
Section: The Effect Of Vision In the Post-stimulation Periodmentioning
confidence: 83%